(untitled) (Scientific Conference on Multidisciplinary Studies, 2025)
It is said that God is closer to every person than their jugular vein. Similarly, the Word of Allah is just as close to every human being. The WORDS that God, out of His mercy, conveyed to the human He created and nurtured — His advice, guidance for living, rules and discipline, His prohibitions and commands — if a person could deeply understand and comprehend all the rulings He has ordained, if they would reflect on them using the full capacity of their intellect, and build their life upon the foundation of divine guidance, then the closeness between God and human, and between the Word and human, would grow stronger and deeper. Allah Himself says that He only commands goodness. He forbids evil, corruption, bloodshed, and the rebellious impulses of the ego, as well as the tragic consequences that follow from them.